UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI MODEL TALKING STICK SISWA KELAS VIIC SMP NEGERI 11 MERANGIN - Suci Nurul Hidayati (Pendidikan Matematika | STKIP YM Bangko, 2016)
This study aims to improve the mathematical problem solving skills of VIIC class students of SMPN 11 Merangin with the talking stick learning model 2014/2015 school year. The method in this study was classroom action research (CAR) which was held in VIIC class 11 of Merangin Middle School 2014/2015 academic year. This study consisted of two cycles, each cycle had three meetings, two material meetings and one test meeting. The subjects of this study were VIIC class students of 11 SMA Merangin 2014/2015 academic year which amounted to 23 students. Data is collected using a written test, observation of student and teacher activities, field notes and student documentation during the learning process takes place. The technical analysis of the data used in this study is the analysis of test results data and analysis of student observations. The results showed mathematical problem solving abilities of class VIIC students of SMP 11 Merangin 2014/2015 academic year increased in each cycle with the results of 63.43% in the first cycle and 78.08% in the second cycle or an increase of 14.65% from the first cycle to cycle II. For student activities also experienced an increase from the percentage of 59% in the first cycle to 80.5% in the second cycle or an increase of 21.5% from cycle I to cycle II. From these results it can be concluded that the talking stick learning model can improve students' mathematical problem-solving skills on the subject of triangles and rectangles. Keywords: Talking Stick, Mathematical Problem Solving Ability